1999
DOI: 10.1074/jbc.274.18.12454
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Is a Zn2+ Metalloprotein

Abstract: Decorin is ubiquitously distributed in the extracellular matrix of mammals and a member of the proteoglycan family characterized by a core protein dominated by leucine-rich repeat motifs. We show here that decorin extracted from bovine tissues under denaturing conditions or produced in recombinant "native" form by cultured mammalian cells has a high affinity for Zn 2؉ Decorin, a small chondroitin/dermatan sulfate proteoglycan, is found in the extracellular matrix of a variety of tissues such as skin (1-3), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
1
35
0
1
Order By: Relevance
“…Expression of Decorin and Decorin Fragments in Escherichia coli-The cloning, expression, and purification of full-length decorin as an MBP fusion protein (MBP-decorin), and of a decorin N-terminal peptide as a GST fusion protein (GST-MD4) and the production of the isolated peptide (MD4) have been described previously (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Decorin and Decorin Fragments in Escherichia coli-The cloning, expression, and purification of full-length decorin as an MBP fusion protein (MBP-decorin), and of a decorin N-terminal peptide as a GST fusion protein (GST-MD4) and the production of the isolated peptide (MD4) have been described previously (23).…”
Section: Methodsmentioning
confidence: 99%
“…1). Recombinant decorin core protein and core protein fragments were expressed as fusion proteins in E. coli, as previously described (23). Control peptides of MBP and GST alone were also purified.…”
Section: Overexpression Of Recombinant Decorin Glycoforms and N-terminalmentioning
confidence: 99%
“…It has been shown that several basement membrane proteins, such as laminin and type IV collagen, directly induce the formation of capillary-like structures in endothelial cells, whereas fragments of these molecules inhibit the process (Sage, 1997). Decorin, found in many tumor beds, is a member of the small leucine-rich proteoglycan superfamily and plays important biological roles through its ability to bind other extracellular matrix proteins, certain growth factors and metal ions (Iozzo, 1999;Kresse and Scho¨nherr, 2001;Yang et al, 1999). Decorin is markedly up-regulated during quiescence in human diploid fibroblasts (Coppock et al, 1993) and vascular smooth muscle cells (Mauviel et al, 1995), but its expression is totally abrogated in most tumor cell lines tested .…”
Section: Introductionmentioning
confidence: 99%
“…Because decorin is a Zn 2ϩ metalloprotein (56), and this cation promotes the binding of decorin to fibrinogen, collagen, fibronectin (57), and myostatin (58), we performed binding experiments in the absence or presence of increasing concentrations (0 -120 M) of ZnCl 2 . Notably, we found no effect of Zn 2ϩ in modulating the binding of recombinant decorin protein core to either IGF-I or IGF-IR (not shown), indicating that this protein-protein interaction is independent of Zn 2ϩ .…”
Section: Igf-ir and Decorin Expression In Bladdermentioning
confidence: 99%